Experimental study on the drainage gas recovery of an environmentally friendly nanofluid in tight gas reservoirs. (7th November 2022) - Guowei, Qin; Qingping, Liu; Xiaohui, Li; Saisai, Sun; Wenlong, Qin; Mei, Wu
Abstract: The efficiency of gas recovery in tight gas reservoirs has been a challenge in the oil and gas industry for the past decade because conventional drainage or water‐controlled gas recovery technologies typically have poor performance in low‐permeability reservoirs. To solve this problem, self‐made nanofluid was introduced to enhance drainage gas recovery in a tight gas reservoir. In this paper, nanofluid was prepared by phase reversal technology for application in a tight gas reservoir. Its thermal, acidic, alkaline, and salty stabilities were systematically investigated by using light transmittance as a shortcut index. At the same time, its biodegradability and biotoxicity were evaluated based on the industry/national standard, and the effectiveness of its drainage gas recovery was studied by dynamic gas–water percolation. The results showed that the self‐made nanofluid can be effectively used for drainage gas recovery in tight gas reservoirs. The nanofluid has chemical stability and is environmentally friendly, which fully conforms to the contemporary development trend of the oil and gas industry. The nanofluid can shift the isotonic point of the gas–water relative permeability to the left (its minimum is 1.83% at 6.25 wt.% and maximum is 4.78% at 100 wt.%) and reduce the irreducible water saturation (its minimum is 8.84% at 6.25 wt.% and maximum is 4.28% at 100 wt.%), achieving the purpose of the enhancement of drainage gas recovery. The research results provide technical support for the application of nanofluid to improve the gas production in tight gas reservoirs.